The Encyclopedia of Philosophy of Religion 2021
DOI: 10.1002/9781119009924.eopr0370
|View full text |Cite
|
Sign up to set email alerts
|

Somānanda

Abstract: Somānanda was a Brahmin of the Kashmir Valley who flourished c. 900–950 ce . He is the founding author of the Śaiva philosophical school known as the Pratyabijñā and is the author of the Śivadṛṣṭi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The ACB clade has substantially increased its repertoire of catabolic pathways for alternative carbon sources compared to taxa outside this clade [94]. For a small number of mostly handpicked A. baumannii strains, previous studies have experimentally confirmed the ability to grow on tricarballylate and putrescine, malonate, butanediol and acetoin, phenylacetate, muconate, glucarate, galactarate (mucate), and 4-hydroxyproline as sole carbon sources [40,85].…”
Section: Carbohydrate Catabolismmentioning
confidence: 99%
“…The ACB clade has substantially increased its repertoire of catabolic pathways for alternative carbon sources compared to taxa outside this clade [94]. For a small number of mostly handpicked A. baumannii strains, previous studies have experimentally confirmed the ability to grow on tricarballylate and putrescine, malonate, butanediol and acetoin, phenylacetate, muconate, glucarate, galactarate (mucate), and 4-hydroxyproline as sole carbon sources [40,85].…”
Section: Carbohydrate Catabolismmentioning
confidence: 99%